Frequency and Antimicrobial Susceptibility Profile of Acinetobacter baumannii Isolated at a Tertiary Care Diagnostic Facility - Hussain, Aamir; Ihsan Ullah Khan; Muhammad Qammar Saeed (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the frequency and antimicrobial susceptibility pattern of Acinetobacter baumannii isolated at a tertiary care setting. Study Design: Cross sectional study. Place and Duration of Study: Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from July to Dec 2018. Methodology: All the specimens submitted, which yielded the growth of Acinetobacter baumannii, were included in the study. Isolates were confirmed biochemically by using api 20NE. Antimicrobial susceptibility was done using standard procedures and as per CLSI’s latest guidelines. Results: Nine thousand nine hundred thirty-one specimens were submitted to the Microbiology Department AFIP for culture and antimicrobial susceptibility testing during the study period. Amongst these, 1633(16.5%) specimens yielded the growth of different pathogens. Of 1633 culture-positive isolates, 101(6.2%) were identified as Acinetobacter baumannii. Among these,34.6% of the isolates were recovered from respiratory specimens, while 29.7% from pus and pus swab specimens. Minocycline was the most sensitive antibiotic with 59.4% sensitivity, followed by Doxycycline, to which 48.5% of isolates were susceptible. Sensitivity to all other antimicrobials was 24% or less. In vitro, sensitivity to Carbapenems is very low. Conclusion: Acinetobacter baumannii was isolated from 6.2% of specimens submitted for culture and susceptibility testing. Minocycline was the most sensitive antibiotic, followed by Doxycycline. Sensitivity to most of the other antimicrobials was 24% or less. An alarming resistant pattern demands strict infection control practices and judicious use of antibiotics.